Development of Vinyl Ester and Reed Composite Material with Weight Fraction of 10% and Reinforcement at Different Orientations - Kazi, Q. A.; Jamali, Q. B.; Bhatti, M. T.; Rajput, U. A.; Kazi, I. A.; Solangi, S. H. (Engineering, Technology & Applied Science Research, 2019)
Composite materials have been used to resolve industrial problems. Considerable attention from the industrial side started in the 1960s with the introduction of polymer-based composite materials. Their advantages such as low weight (density), resistance to corrosion, high strength and low maintenance cost made composite materials an attractive substitute to conventional materials. A new composite material was developed with 10% natural fiber at 0o, 90o and 0/90o orientations resulting in ample improvements in the mechanical properties as compared to previous studies. The sample at 0/90o orientation gives the best results with tensile, tensile strength, tensile elongation and Young’s Modulus values of 2458.19N, 4594.5MPA, 4.7% and 23.0 respectively